Analisis Kajian Kontransif Afiksasi Verba Prefiks Nge- Dialek Jawa Kronjo Banten dalam Dialek Bahasa Indonesia: Analysis of The Study of Contrastive Affixation of Prefix Verbs Nge- in The Javanese Dialect of Banten Kronjo in Indonesian Dialect - Rokmah, Rokmah (Kibas Cenderawasih, 2024)
This study aims to identify and find out related to the contrastive analysis of affixation of prefix verbs Nge- Javanese Kronjo Banten in Indonesian. The method used is descriptive qualitative. Techniques and data sources, namely through interviews. The results and discussion found similarities and differences between Javanese kronjo Banten and Indonesian. The difference is seen from the affixation of the verb to form the prefix. but for the similarities seen from the meaning or meaning of the word. Affixation of the prefix verb Nge- in Javanese Kronjo Banten when it is Indonesianized, the prefix changes to the prefix {Me-, Men-, Mem-, and Meng-}.